Formation pathway for lonely stripped-envelope supernova progenitors: implications for Cassiopeia A. Issue 1 (23rd September 2020) - Hirai, Ryosuke; Sato, Toshiki; Podsiadlowski, Philipp; Vigna-Gómez, Alejandro; Mandel, Ilya
ABSTRACT: We explore a new scenario for producing stripped-envelope supernova progenitors. In our scenario, the stripped-envelope supernova is the second supernova of the binary, in which the envelope of the secondary was removed during its red supergiant phase by the impact of the first supernova. Through 2D hydrodynamical simulations, we find that ∼50–90 ${{\ \rm per\ cent}}$ of the envelope can be unbound as long as the pre-supernova orbital separation is ≲5 times the stellar radius. Recombination energy plays a significant role in the unbinding, especially for relatively high mass systems (≳18 M⊙ ). We predict that more than half of the unbound mass should be distributed as a one-sided shell at about ∼10–100 pc away from the second supernova site. We discuss possible applications to known supernova remnants such as Cassiopeia A, RX J1713.7−3946, G11.2−0.3, and find promising agreements. The predicted rate is ∼0.35–1${{\ \rm per\ cent}}$ of the core-collapse population. This new scenario could be a major channel for the subclass of stripped-envelope or type IIL supernovae that lack companion detections like Cassiopeia A.